An Ambitious Objective: an Assessment of the EU R&D Strategy - Andreas Schibany; Gerhard Streicher (Foresight and STI Governance, 2008)
In Barcelona, the European Union set ambitious targets for the European Research Area, calling for research expenditures equivalent to 3 % of Europe’s GDP by 2010. This paper analyses the implications of these targets, assesses the influence of the member states, and examines the role of the private sector in reaching the targets.